2017
DOI: 10.1130/g38860.1
|View full text |Cite
|
Sign up to set email alerts
|

Paleofluvial and subglacial channel networks beneath Humboldt Glacier, Greenland

Abstract: The identification of subglacial drainage systems can inform our understanding of past and present hydrological processes, landscape evolution, and ice dynamics. Here, we present evidence from satellite imagery, digital elevation models, and radio-echo sounding data for a series of channelized networks with contrasting paleofluvial and subglacial origins beneath Humboldt Glacier, northern Greenland. A >250-km-long, dendritic paleofluvial channel network beneath the northern portion of Humboldt is interpreted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 26 publications
(36 reference statements)
3
45
0
Order By: Relevance
“…More generally, however, the relative rarity of high abruptness in thawed regions is in agreement with hydrological potential analysis (Livingstone et al, 2013), which predicts that deep subglacial lakes are both rare and small in the north-west of the GrIS. Instead, channelised drainage networks -such as the system recently identified beneath Humboldt glacier (Livingstone et al, 2017) -are likely to be common in thawed regions (and are consistent with the generally diffuse scattering signature that we observe).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…More generally, however, the relative rarity of high abruptness in thawed regions is in agreement with hydrological potential analysis (Livingstone et al, 2013), which predicts that deep subglacial lakes are both rare and small in the north-west of the GrIS. Instead, channelised drainage networks -such as the system recently identified beneath Humboldt glacier (Livingstone et al, 2017) -are likely to be common in thawed regions (and are consistent with the generally diffuse scattering signature that we observe).…”
Section: Discussionsupporting
confidence: 61%
“…For Greenland, this self-affine statistical landscape classification could be integrated with existing knowledge of geology (e.g. Henriksen, 2008) and larger-scale landscape features including subglacial drainage networks (Cooper et al, 2016;Chu et al, 2016;Livingstone et al, 2017) and palaeofluvial canyons (such the "mega canyon" feature observed in Fig. 6e, which has Petermann glacier as its modern-day terminus) (Bamber et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…This includes the dendritic flow path networks in the Jakobshavn (Cooper et al, 2016) and Humboldt catchments (Livingstone et al, 2017), along with the prominent…”
Section: Basal Water Bed Topography and Subglacial Flow Pathsmentioning
confidence: 99%
“…10(b)) can potentially be linked to our understanding of the seasonal evolution of the subglacial drainage system. Specifically, in regions where there is 550 significant surface melt-water forcing, efficient channelised drainage systems can form during the summer months, which can result in a substantial lack of winter-time water storage in faster moving subglacial troughs (Chu et al, 2016).…”
mentioning
confidence: 99%
“…The presence of vertical walls undoubtedly indicates that the structural heritage had a preponderant influence in the shaping of the basement. Moreover, a pre‐existing network of fluvial valleys was potentially reworked and amplified by direct glacial abrasion (von Brunn, , ), as is the case for some Quaternary high‐latitude valleys that originated from the combination of both pre‐glacial fluvial and glacial erosion processes (Lajeunesse, ; Livingstone et al , ). Indeed, the major hiatus that separates the basement from the Dwyka Group suggests that the study area constituted an emerged domain during pre‐Dwyka times as a result of crustal uplift preceding the inception of the Karoo Basin and the onset of glaciation (Visser, ; Tankard et al , ) and onto which a fluvial system may well have developed.…”
Section: Interpretations: Depositional Environments Ice‐margin Fluctmentioning
confidence: 99%